The SiO2:TiO2 hybrid biodegradable nanolubricant for sustainable machining: The stability, thermo-physical and tribology perspectives - Nurlisa, Hamzan; Irnie Azlin, Zakaria; Jaharah, Abdul Ghani; Nurul Hayati, Abdul Halim; Wan Azmi, Wan Hamzah; Zainoor Hailmee, Solihin; Ahsana Aqilah, Ahmad (Elsevier Ltd, 2025)
The increase in awareness of environmental issues and economic concerns has enabled the emergence of sustainable machining termed Minimum Quantity Lubrication (MQL). However, the extreme conditions of high-speed cutting hard-to-cut materials have posed new challenges for MQL machining. Thus, the Nano MQL (NMQL) is introduced. In this research, hybrid SiO₂:TiO₂ nanoparticles are dispersed in a biodegradable base oil, and the stability, thermo-physical properties, and tribological perspectives are comprehensively investigated. Five volume concentrations of hybrid SiO₂:TiO₂ nanolubricants ranging from 0.01 % to 0.1 % volume concentration were investigated and compared against the base oil. In summary, 0.1 vol% hybrid SiO₂:TiO₂ in biodegradable base oil has demonstrated characteristics of potential advanced lubrication in MQL machining application